Primary intestinal lymphangiectasia in an elderly female patient: A case report on a rare cause of secondary immunodeficiency. Issue 31 (August 2017) - Huber, Xaver; Degen, Lukas; Muenst, Simone; Trendelenburg, Marten
Abstract : Abstract: Protein loss via the gut can be caused by a number of gastrointestinal disorders, among which intestinal lymphangiectasia has been described to not only lead to a loss of proteins but also to a loss of lymphocytes, resembling secondary immunodeficiency. We are reporting on a 75-year-old female patient who came to our hospital because of a minor stroke. She had no history of serious infections. During the diagnostic work-up, we detected an apparent immunodeficiency syndrome associated with primary intestinal lymphangiectasia. Trying to characterize the alterations of the immune system, we not only found hypogammaglobulinemia and lymphopenia primarily affecting CD4+, and also CD8+ T cells, but also marked hypocomplementemia affecting levels of complement C4, C2, and C3. The loss of components of the immune system most likely was due to a chronic loss of immune cells and proteins via the intestinal lymphangiectasia, with levels of complement components following the pattern of protein electrophoresis. Thus, intestinal lymphangiectasia should not only be considered as a potential cause of secondary immune defects in an elderly patient, but can also be associated with additional hypocomplementemia.